An unusual presentation of vulvar cavernous hemangioma in a 10-year-old premenarchal girl: a rare entity - Verma, Aruna; Sharma, Garima; Srivastava, Neelu; Verma, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Vascular tumors of the female genitalia are unusual. Hemangiomas are benign tumors of the blood vessels. Usually they are asymptomatic but may present as discomfort, pain and other symptoms. However, vulvar cavernous hemangioma can be seen in newborns and infants, but rarely occur in children and adult women. A 10-year old premenarchal girl presented with a painless swelling on her right labia majora since birth which was increasing gradually. On examination, a well-defined, soft, mobile and non-tender multicystic swelling was observed involving right labia majora and minora of approximately 5×6 cm in size. An ultrasound of the lesion showed a well-circumscribed, hypo echoic mass with multicystic lesion of size 40×14×44 mm arising from right labia majora with vascularity on color Doppler and venous flow on spectral pattern, suggestive of vascular malformation. Surgical excision of lesion was performed with the utmost care to preserve the surrounding healthy tissue and vulvar anatomy. Histopathological examination (HPE) report confirmed the diagnosis of a cavernous hemangioma with no evidence of malignancy. Vulvar cavernous hemangioma is an uncommon vascular tumor that can be rarely seen in pediatric patients. Imaging studies, such as ultrasound and magnetic resonance imaging (MRI), play a crucial role in confirming the diagnosis and guiding the management. Surgical excision with preservation of healthy tissue is the treatment of choice. Long-term follow-up is essential to monitor recurrence and patient's well-being.